Attitude and compliance with PPE use to prevent cross-infection - Rida Khoerunisa; Anita Roslinawati; Hera Nurnaningsih; Nining Ningrum (Indonesian Journal of Dental Medicine, 2026)
Background: Infection transmission in medical settings can occur due to a lack of attention to preventive measures. Standard precautions, such as the use of personal protective equipment and hand hygiene, are crucial to reduce this possibility. Purpose:  The purpose of this study was to measure the extent of the attitudes and compliance of three-year dental health diploma students at the Bandung Ministry of Health Polytechnic in implementing the use of personal protective equipment while working in dental clinics. Methods:  A quantitative descriptive approach was adopted as the method for this study. The instrument used was a questionnaire containing aspects of attitude and compliance with the use of personal protective equipment as a measure to prevent cross-infection. The research data analysis used was univariate analysis. Attitudes and compliance were divided into three categories: good (>75), moderate (55-75%), and poor (<50%).3 Personal protective equipment included in this research questionnaire are gloves, masks, protective goggles, and protective gowns.  Results: The data showed that most participants' attitudes were in the adequate category (70%), while compliance levels were almost balanced between the adequate category (51%) and the good category (47%). Conclusion:  The use of gloves, face masks, and gowns during treatment was consistent. The respondents demonstrated adequate attitudes and compliance levels in applying personal protective equipment to prevent cross-infection.